T2_Oral_questions

T2_Oral_questions - loga(M N = Review 1 loga(M N = logaM logaN log of product = sum of logs Review 2 loga M = N Review 3 loga M = logaM logaN N log

This preview shows pages 1–44. Sign up to view the full content.

log a ( M · N ) = Review 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
log a ( M · N ) = log a M + log a N log of product = sum of logs Review 2
log a ( M N ) = Review 3

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
log a ( M N ) = log a M - log a N log of quotient = diﬀerence of logs Review 4
log a M + log a N = Review 5

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
log a M + log a N = log a ( M · N ) sum of logs = log of product Review 6
log a M - log a N = Review 7

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
log a M - log a N = log a ( M N ) diﬀerence of logs = log of quotient Review 8
log a M r = Review 9

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
log a M r = rlog a M Power can be brought to the front of the log. Review 10
Solve this question Review 11

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Review 12
Solve this question Review 13

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Review 14
Rewrite 1 x m with x on the numerator. Review 15

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
1 x m = x - m When moving from the denominator to numerator, the SIGN of the power changes to the opposite sign. Review 16
Rewrite x - m with x on the denominator. Review 17

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
x - m = 1 x m When moving from the numerator to denominator, the SIGN of the power changes to the opposite sign. Review 18
x - 3 = 27 x = Review 19

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
x - 3 = 27 1 x 3 = 27 1 = 27 x 3 1 27 = x 3 1 3 = x Review 20
x - 3 = 1 27 x = Review 21

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
x - 3 = 1 27 1 x 3 = 1 27 27 · 1 = x 3 · 1 27 = x 3 3 = x Review 22
1 e = Review 23

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
1 e = e - 1 Review 24
( 1 e ) (2 - 4 x ) = Review 25

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
( 1 e ) (2 - 4 x ) = ( e - 1 ) (2 - 4 x ) = e - 2+4 x Review 26
ln 1 8 = Review 27

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
ln 1 8 = ln 8 - 1 = - ln 8 Review 28
log a a = Review 29

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
log a a = 1 Review 30
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 05/23/2011 for the course MAC 1147 taught by Professor Nuegyen during the Spring '11 term at FSU.

Page1 / 118

T2_Oral_questions - loga(M N = Review 1 loga(M N = logaM logaN log of product = sum of logs Review 2 loga M = N Review 3 loga M = logaM logaN N log

This preview shows document pages 1 - 44. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online